Pengaruh Kepuasan Pemberian Gaji Terhadap Etos Kerja Pegawai Kontrak Pelabuhan Perikanan Samudera Bungus - Risdayani, Risdayani; Novi Yanti (Ekasakti Matua Jurnal Manajemen, 2024)
The purpose of this study was to analyze and find out: 1. The dominant indicator of the variable of salary satisfaction and work ethic 2. The effect of the variable of salary giving on work ethic. The population of this research is the contract employees of the Bungus Ocean Fishing Port as many as 34 people. The sampling technique of this study used the total sampling method. The data analysis method in this study used descriptive analysis, multiple linear regression analysis, coefficient of determination and hypothesis testing t. The results of the analysis show that 1. The dominant indicator in the variable of salary satisfaction is an indicator of a decent standard of living with a TCR value of 81.5%. The dominant indicator in the work ethic variable is discipline with a TCR value of 83.6% which is in good criteria. 2 Salary has a positive and significant effect on work ethic. offering a salary has a contribution to the work ethic of contract employees at the Bungus Ocean Fishing Port by 82.9 the remaining 17.1% damaging the influence of this research variable, one of which is work spirit, education, organizational commitment, organizational culture and others.